2013
DOI: 10.1115/1.4023605
|View full text |Cite
|
Sign up to set email alerts
|

Jet-Surface Interaction Test: Far-Field Noise Results

Abstract: Many configurations proposed for the next generation of aircraft rely on the wing or other aircraft surfaces to shield the engine noise from the observers on the ground. However, the ability to predict the shielding effect and any new noise sources that arise from the high-speed jet flow interacting with a hard surface is currently limited. Furthermore, quality experimental data from jets with surfaces nearby suitable for developing and validating noise prediction methods are usually tied to a particular vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The noise enhancement at 30 • , however, is virtually negligible. This is consistent with the earlier findings 2,8,9,13,18,27,28 and the edge-scattering mechanism proposed in the earlier paper 23 (at low frequencies, the scattered sound has a dipolar, rather than a cardioid directivity pattern). In the intermediate-and high-frequency range, jet noise is effectively shielded by the flat plate at angles close to 90 • to the jet axis, while these shielding effects diminish at lower observer angles.…”
Section: Jet Noise Spectrasupporting
confidence: 93%
“…The noise enhancement at 30 • , however, is virtually negligible. This is consistent with the earlier findings 2,8,9,13,18,27,28 and the edge-scattering mechanism proposed in the earlier paper 23 (at low frequencies, the scattered sound has a dipolar, rather than a cardioid directivity pattern). In the intermediate-and high-frequency range, jet noise is effectively shielded by the flat plate at angles close to 90 • to the jet axis, while these shielding effects diminish at lower observer angles.…”
Section: Jet Noise Spectrasupporting
confidence: 93%
“…However, examination of the acoustic properties of the low frequency installed noise and its dependence on the engine position, jet condition and flap position leads one to believe that the dominant effect is the trailing-edge noise. This is because the dipole characteristics are in agreement with the observed directivity pattern of trailing-edge noise at low frequencies (Head & Fisher 1976;Wang 1981;Mead & Strange 1998;Bondarenko et al 2012;Brown 2013;Amiet 1976b;Roger & Moreau 2005), decreasing L results in a reduced noise and a frequency shift toward high frequencies (Head & Fisher 1976;Way & Turner 1980;Stevens et al 1983;Wang 1981;Shearin 1983), there exists a high correlation between the pressure field near the trailing edge and the far-field sound (Head & Fisher 1976) and the dependence of sound intensity on the characteristic jet velocity is to the 5 to 6 power (Head & Fisher 1976;Brown 2013). These trailing-edge noise characteristics remind us the suitablity of Amiet's approach in modelling the low-frequency installed jet noise.…”
Section: Introductionsupporting
confidence: 78%
“…Many investigations followed and they fall roughly into three categories: identifying installed noise sources by studying the acoustic characteristics of an installed jet, the engine position, jet condition and flap position effects; developing installed jet noise prediction models; and investigating noise reduction techniques. The first category includes the experimental work of Head & Fisher (1976), Szewczyk (1979), Way & Turner (1980), Shearin (1983), Mead & Strange (1998) and Brown (2013). Through their experimental work, it was found that increasing H results in less noise at low frequencies and decreasing L follows the same trend and shifts the peak frequency to higher frequencies, the velocity dependence of the peak of the low frequency augmentation is to the five to sixth power.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of the noise generated by the interaction of a circular jet with the trailing edge of a flatplate were carried out by Brown (2013Brown ( , 2015a in the Small Hot Jet Acoustic Rig (SHJAR) at the Aero-Acoustic Propulsion Laboratory (AAPL) at NASA Glenn Research Center (Bridges and Brown, 2005;Brown and Bridges, 2006). The experimental configuration along with the relevant geometric parameters are shown in figure 4.…”
Section: Numerical Resultsmentioning
confidence: 99%